EFFECT OF MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT PRIVATE UNIVERSITIES IN BANDUNG - Wardoyo, Trimanto Setyo; Budiningsih, Tatik (2021)
This study aims to determine how the motivation, job satisfaction and employee performance at private universities in Bandung and the effect of motivation and satisfaction on performance. Using the purposive sampling method, a research sample of 81 people consisting of 42 lecturers and 39 non-lecturers has been successfully obtained. The results showed that the motivation, job satisfaction, and employee performance at private universities in Bandung were high, but the group of lecturers had much higher motivation, job satisfaction, and performance than the group of non-lecturers. Motivation and job satisfaction simultaneously have a significant effect on employee performance at private universities in Bandung. Motivation and job satisfaction partially have a significant effect on employee performance at private universities in Bandung. However, based on a partial analysis, it is also revealed that the motivation of non-lecturer employees, with a significance level (α) of 5%, had no significant effect on the performance of the non-lecturer employees. The follow-up findings show that the group of non-lecturers is better at maintaining punctuality in clocking in to the office and in establishing organizational relationships with their superiors than the group of lecturers.